Inverting the Solvatochromism of Pyridinium-N-Phenolate Dyes by the Addition of a Second Pyridinium Unit - Aliaga-Vidal, C; Aliaga-Vidal, C; Dominguez-Caru, M; Vidal-Palomo, M; Vidal-Palomo, M (American Chemical Society, 2024)
Three bipyridinium phenolates were synthesized, and their spectral behavior was recorded at various solvent polarities and compared to a classic pyridinium phenolate dye possessing only one pyridinium acceptor ring in its structure. The addition of a second pyridinium unit to the classic solvatochromic core results in an unexpected change in the spectral behavior from negative solvatochromism (displacement of the absorption band to shorter wavelengths) to inverted solvatochromism, characterized by the transition from negative to positive solvatochromism (displacement of the absorption band to longer wavelengths) at moderate solvent polarities. © 2024 American Chemical Society.